2012
DOI: 10.1007/s00262-012-1359-5
|View full text |Cite
|
Sign up to set email alerts
|

Serum-free freezing media support high cell quality and excellent ELISPOT assay performance across a wide variety of different assay protocols

Abstract: Robust and sensitive ELISPOT protocols are commonly applied concomitant with the development of new immunotherapeutics. Despite the knowledge that individual serum batches differ in their composition and may change properties over time, serum is still commonly used in immunologic assays. Commercially available serum batches are expensive, limited in quantity and need to be pretested for suitability in immunologic assays, which is a laborious process. The aim of this study was to test whether serum-free freezin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Therefore, an important aspect is to ensure that the measurement and reporting of the results obtained are comparable between laboratories so that it is easier to interpret and value the data generated. In the last decade a huge effort, undertaken by the Association of Cancer ImmunoTherapy's (CIMT's) immunoguiding program [125] and Cancer Immunotherapy Consortium (CIC) [126], has focused on this in the realm of human studies, and this has successfully led to: (i) a strong awareness of the need to harmonize or standardize measurements, (ii) to technical improvements and harmonization of the assays used, and (iii) to more transparent reporting [127][128][129]. It can be envisaged that similar efforts by scientists performing studies in mouse tumor models will lead to a quicker design of immunotherapeutic strategies, which expedite the translation to the treatment of patients.…”
Section: Immunoguiding Is Important For the Development Of Immunothermentioning
confidence: 99%
“…Therefore, an important aspect is to ensure that the measurement and reporting of the results obtained are comparable between laboratories so that it is easier to interpret and value the data generated. In the last decade a huge effort, undertaken by the Association of Cancer ImmunoTherapy's (CIMT's) immunoguiding program [125] and Cancer Immunotherapy Consortium (CIC) [126], has focused on this in the realm of human studies, and this has successfully led to: (i) a strong awareness of the need to harmonize or standardize measurements, (ii) to technical improvements and harmonization of the assays used, and (iii) to more transparent reporting [127][128][129]. It can be envisaged that similar efforts by scientists performing studies in mouse tumor models will lead to a quicker design of immunotherapeutic strategies, which expedite the translation to the treatment of patients.…”
Section: Immunoguiding Is Important For the Development Of Immunothermentioning
confidence: 99%
“…ELISPOT assay and multimer staining, have been the subject of a number of harmonisation studies, in particular in the fields of infectious diseases [ 1 , 5 ] and cancer, where large proficiency panels have been conducted both in Europe and the United States within the remit of the Association for Cancer Immunotherapy Immunoguiding Programme (CIMT-CIP) [ 6 ] and the Cancer Immunotherapy Consortium of the Cancer Research Institute (CIC-CRI) [ 7 ], respectively. Such panels have investigated factors that influence the frequency of responses detected by ex vivo IFNγ ELISPOT [ 6 , 8 , 9 ] and multimer staining [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Olson and colleagues formally tested conditions for shipping fresh blood to be used in T cell assays at central labs and found that maintaining specimen temperature above 22 °C or preferably near 30 °C was optimal [75]. Filbert et al defined methods for cryopreservation that yielded optimal T cell responses in subsequent ELISPOT analysis [76]. And perhaps, most importantly, the reporting of immune readouts has been addressed by the publication of minimal information about T cell assays (MIATA) in an effort to harmonize assays between laboratories [77••].…”
Section: Immune Monitoring Of Vaccine Efficacymentioning
confidence: 99%